1996
DOI: 10.1159/000196520
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Modifies the Total Lung Capacity in Smokers

Abstract: Smoking-related airflow obstruction can develop with or without emphysema. Moderate alcohol consumption has been suggested to diminish the risk of centrilobular emphysema caused by smoking. Our aim was to study the influence of total energy and nutrient (protein, fat, carbohydrate and alcohol) intake on smoking-related emphysema. Lung function and nutrient intake including alcohol consumption were recorded at the age of 68 years in 478 men as part of the population study ‘Men Born in 1914’ in Malmö, Sweden. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Alcohol consumption is associated with a significant decline in lung capacity. [11] Tobacco use is widely prevalent among substance using patients in treatment settings. A national level treatment center in India reported tobacco use along with co-morbid alcohol use in 36.4% of subjects coming to a tobacco cession clinic.…”
mentioning
confidence: 99%
“…Alcohol consumption is associated with a significant decline in lung capacity. [11] Tobacco use is widely prevalent among substance using patients in treatment settings. A national level treatment center in India reported tobacco use along with co-morbid alcohol use in 36.4% of subjects coming to a tobacco cession clinic.…”
mentioning
confidence: 99%
“…Others have also reported positive associations of wine intake with FEV 1 % and FVC%, 23,24 showing a possible protective effect of alcohol on pulmonary function 25,26 . However, other studies have found negative associations between heavy drinking and pulmonary function 27–29 or no associaton 30,31 . In the present study, 99% of drinkers were light/moderate drinkers, which was reflected in the average daily consumption of pure alcohol: 5.8 g for males and 1.3 g for females (compared with 27.3 g for Japanese males in Japan 13 ).…”
Section: Discussionmentioning
confidence: 98%
“…Some, but not all, previous studies have shown a negative association of alcohol intake with pulmonary function. [18][19][20][21][22][23][24][25] Taking all studies together, total alcohol intake might not be strongly associated with pulmonary function, but the underlying reason for the conflicting evidence may, at least in part, be related to the failure of studying beverage-specific al-cohol in most of these studies. Our study supports this latter hypothesis.…”
Section: Discussionmentioning
confidence: 99%